Lung function: population epidemiology and concordance in Australian children aged 11–12 years and their parents. (4th July 2019) - Welsh, Liam; Kathriachchige, Gayan; Raheem, Tahmeed; Grobler, Anneke C; Wake, Melissa; Ranganathan, Sarath
Abstract : Objectives: To describe the epidemiology of lung function in Australian children aged 11–12 years and their parents, and explore the degree of intergenerational concordance. Design: Cross-sectional study (the Child Health CheckPoint) nested in the Longitudinal Study of Australian Children (LSAC). Setting: Assessment centres in seven Australian cities and eight regional towns, February 2015 to March 2016. Families unable to attend a clinic appointment were offered a home visit during the same period. Participants: 1874 families (53% of all eligible) participated in the study. Lung function data were available for 1759 children aged 11–12 years and 1774 parents (1668 biological pairs). Outcome measures: Participants completed spirometry with measures including forced expiratory volume in 1 s (FEV1 ), forced vital capacity (FVC) and mid expiratory flow (MEF), converted to z-scores using Global Lung Initiative equations. Parent–child concordance was assessed using Pearson's correlation coefficients and multivariable linear regression models. Survey weights and methods accounted for LSAC's complex sampling, stratification and clustering within postcodes. Results: All lung function measures followed approximately normal distributions. Mean (SD) for FEV1, FVC and MEF z-scores in children were 0.33 (1.07), 0.83 (1.14) and −0.48 (1.09), respectively. Mean (SD) in parents were 0.28 (1.10), 0.85 (1.15) and −0.45 (1.10), respectively. Parent FEV1, FVC and MEF were associated with child lung function with significant positive correlation coefficients (0.22, 95% CI 0.17 to 0.26; 0.24, 95% CI 0.20 to 0.29; and 0.24, 95% CI 0.20 to 0.29, respectively). Conclusions: Mean lung volumes were larger but with smaller airway size than international standards for both parents and children in this population sample. Modest associations between parent and child lung function highlight the potential for better identification of 'at risk' populations. Therefore, these findings may aid the development of health policy that aims to prevent the onset or limit the progression of lung disease.